Efikasi Pestisida Hayati pada Padi Varietas Tahan Tungro - Arif Muazam; Nurkholish Nugroho (Universitas Muhammadiyah Purworejo, 2020)
Sidrap as a rice granary center in South Sulawesi, plays an active role in efforts to self-sufficiency in eastern Indonesian food in particular and NKRI in general. The efforts of integrated rice cultivation have been carried out as an effort to achieve national food independence. This paper discusses the population density of green leafhoppers, predatory insects, and other pests in the Inpari 36 rice crop as tungro (new released) varieties in endangered areas, the study was carried out in the experimental garden area of Tungro Disease Research, using a Completely Randomized Design (CRD) 2 plot plots of plant varieties of 10 x 10 m2 with 4 replications. The most common adult green leafhopper (Nephotetic verescens) results in Inpari 36 varieties without bioprotector treatment. Natural predators that were fluctuated every week were dominant observations, namely: Agriocnemis spp, Micraspis sp, Conocephalus longipennis, Araenus inustus, Lycosa pseudoannulata, Oxyopes javanacus, and Tetraghenata maxilosa. While at 6-7 MST (weeks after planting) Ophionea nigrofasciata species appeared and in 7MST there were species of Anaxipa longipennis.